The OAS at Seventy Years - Arrighi, Jean-Michel (2018)
In 2018, the OAS celebrates seventy years of its creation. After a brief presentation on the evolution of its founding Charter of 1948 and of the Inter-American System from its inception at the end of the 19th century until the entry of the last members of the OAS in 1991, this article gives a succinct account of the successes achieved by the Organization throughout its existence, highlighting the achievement of relative peace among its member states provided by the construction of an Inter-American normative and institutional fabric based on the fundamental principles of legal equality of States, non-intervention, respect for international law and peaceful settlement of disputes.Subsequently, the article reviews the evolution of these principles during the seventy years of the Organization and the notable progress made, primarily in the development of a regional system for the protection of human rights and for the defense of representative democracy in the Hemisphere. Finally, the article highlights other more recent legal developments in the field of private international law, access to information, combating corruption, organizedcrime and drug trafficking, as well as legal and judicial cooperation.In the end, the article provides a review of the results achieved by the OAS vis-à-vis the emergence of new subregional organizations. These new organizations have not managed to replace the OAS as the political space of legal elaboration, defense of rights human rights and democracy, unique in the region, which encompasses all of its member states on an equal footing.